2019
DOI: 10.2147/amep.s220390
|View full text |Cite
|
Sign up to set email alerts
|

<p>Teaching Medical Students About Attention Deficit Hyperactivity Disorder (ADHD): The Design And Development Of An E-Learning Resource</p>

Abstract: In this paper, we describe how an e-learning resource on Attention Deficit Hyperactivity Disorder (ADHD) for medical students was designed and developed. The aim of the resource was to provide students with essential knowledge and understanding about ADHD prior to their attendance at a classroom teaching session as well as to serve as a revision tool. The paper focuses on the way in which instructional design, educational and multimedia principles were used to inform the development of the resource. It also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This study has demonstrated that a novel e-learning package can successfully be used to teach DRM to UG medical students. Previous studies have been shown that e-learning can be as effective as F2F teaching when it comes to understanding knowledge aspects such as simple recall and comprehension ( 23 26 ). In contrast to the higher levels of learning outline in the Bloom's taxonomy, such as analysis, application, synthesis, and assessment, recall, and comprehension levels of learning are particularly well-served by e-learning.…”
Section: Discussionmentioning
confidence: 99%
“…This study has demonstrated that a novel e-learning package can successfully be used to teach DRM to UG medical students. Previous studies have been shown that e-learning can be as effective as F2F teaching when it comes to understanding knowledge aspects such as simple recall and comprehension ( 23 26 ). In contrast to the higher levels of learning outline in the Bloom's taxonomy, such as analysis, application, synthesis, and assessment, recall, and comprehension levels of learning are particularly well-served by e-learning.…”
Section: Discussionmentioning
confidence: 99%
“…There is instant feedback throughout the learning activities to help raise student’s confidence, motivation and allow them to monitor their progress. 8 The e-learning resource was completed with further reading for the learner that would assist in consolidating their knowledge gained.
Figure 7 Quiz slide.
…”
Section: Methods – Putting Theory Into Practicementioning
confidence: 99%
“… 42 It must be noted, however, that this paper reports preliminary evaluation, and although positive, a more comprehensive evaluation is recommended to ascertain the impact and value of the tool. 8 , 43 This could be expanded for example, by examining further and in-depth the long-term impact, change in behaviour and confidence in medical students with regards to chest x-rays and attitudes towards the topic.…”
Section: Conclusion and Future Implicationsmentioning
confidence: 99%
See 2 more Smart Citations